Video Project to Enhance Comprehension of TOEIC Material - Eva Fachriyah; Ratu Dea Mada Badriyah (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to investigate the application of video project to comprehend TOEIC materials in the